Hapaline appendiculata (Araceae: Caladieae) rediscovered - Boyce, P.C; Kisai, Jelend; Tisai, Jepom (Singapore Botanical Garden, 2005)
Hapaline appendiculata Ridl., a species endemic to Sarawak, Borneo, and hitherto known from only three collections, has recently been recollected. An expanded description for the species, first ever published field photographs and a key to Hapaline in Borneo is presented.